Arc-resistant high-strength conductive aluminum-zirconium-scandium-rare earth alloy and precision casting and forging preparation method of ultra-high voltage GIS conductive support seat

CN122879559APending Publication Date: 2026-10-09JIANGSU XINSHENG ELECTRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611182567.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-09

AI Technical Summary

Benefits of technology

[0017]与现有技术相比,本发明的有益效果为:本发明采用钪锆铈铒复合稀土协同微合金化体系,并配套三套专属定量调控模型,有效破除铝合金强度与导电性能相互制约的行业固有难题,内部生成的核壳纳米析出相可同步实现强化基体与降低电子散射双重作用;依托电弧侵蚀预测模型定向调控稀土配比,电弧热冲击下构件表面能够生成稳定耐高温防护层,显著削弱电弧烧蚀损伤,无需增大构件截面尺寸即可满足设备绝缘防护需求;借助晶粒定量管控模型配合半固态原位锻压工艺,从凝固源头抑制疏松、粗大晶粒等内部缺陷,长期载流运行不易出现局部过热与蠕变形变问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879559A_ABST
    Figure CN122879559A_ABST
Patent Text Reader

Abstract

The application provides a high-strength electrically conductive aluminum-zirconium-scandium-rare earth alloy and a precision casting and forging preparation method of a super-high voltage GIS electrically conductive support seat. The alloy takes high-purity aluminum as a matrix, is compounded with scandium, zirconium, cerium-erbium composite rare earth and a grain refiner, strictly controls harmful impurities, adjusts and controls element ratio to form a specific core-shell nano precipitate phase. Three types of coupled quantitative models are constructed to control the strength and electric conductivity, arc ablation loss and grain size, and to solve the problems of strength and electric conductivity mutual exclusion, arc erosion and casting blank defects. The preparation adopts a semi-solid low-pressure filling combined with an in-situ sealed casting and forging integrated process, is subjected to solid solution + double-stage aging heat treatment, and is then subjected to finishing and electrically conductive protection treatment. The application can refine grains, eliminate internal pore defects, greatly inhibit arc ablation, and the component has high electric conductivity and high mechanical strength, the forming process is simplified, the performance is stable and controllable, and the application is suitable for large-scale production of super-high voltage GIS electrically conductive support components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of special conductive aluminum alloys for power transmission and transformation and precision casting and forging manufacturing technology, specifically to an arc-resistant, high-strength conductive aluminum-zirconium-scandium rare earth alloy and its precision casting and forging preparation method for ultra-high voltage GIS conductive support base. Background Technology

[0002] Ultra-high voltage GIS conductive support bases bear the triple functions of busbar positioning, current carrying and conduction, and insulation support. They withstand long-term high-frequency current, instantaneous short-circuit arc thermal shock, and cyclic mechanical loads. Existing commercial A356 and 6063 aluminum alloys have three major bottlenecks: Strength and conductivity are mutually exclusive: conventional strengthening elements distort the crystal lattice through solid solution, which intensifies the scattering of free electrons. As a result, the conductivity decreases significantly when the strength is increased, making it impossible to simultaneously meet the requirements of high current carrying capacity, low heat generation, and structural load-bearing capacity. The highest tensile strength of existing scandium-free aluminum rare earth alloys is only 260 MPa, which cannot resist short-circuit electrodynamic deformation.

[0003] Extremely poor resistance to arc erosion: The instantaneous temperature of the short-circuit arc in GIS exceeds 6000K, and the surface of ordinary aluminum castings melts and vaporizes rapidly, forming uneven ablation pits. The electric field distortion causes local field strength concentration, which induces insulation breakdown. There is no quantitative arc erosion control model for existing alloys, and passive protection is only achieved by increasing the wall thickness, which greatly increases the size and weight of the equipment.

[0004] The split molding process has serious defects: the traditional process consists of casting blank + rough machining + forging strengthening, which introduces processing stress and interface defects through multiple processes; the cast grains are coarse (≥120μm), with an internal shrinkage porosity of 0.8%~1.5%, Joule heat accumulation in the pores during current carrying, creep deformation during long-term operation, and excessive local temperature rise in GIS; there is no quantitative control formula for grain size by casting and forging, and the heat treatment process is entirely based on experience and adjustment, resulting in large batch performance fluctuations.

[0005] Existing Al-Sc binary alloys only focus on heat resistance strengthening, without the addition of Zr and Ce-Er composite rare earth elements, and lack a core-shell precipitate phase synergistic arc resistance design. At the same time, there is a lack of a quantitative forming method for casting and forging integrated with the complex cavity structure of GIS support bases, and there are no three sets of coupled calculation formulas for arc loss, strength-conductivity balance, and grain refinement. The material and process compatibility is poor, making it difficult to meet the long-term safe operation requirements of megavolt high-voltage equipment. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the existing technology and to propose a method for precision casting and forging of an arc-resistant, high-strength, conductive aluminum-zirconium-scandium rare earth alloy and its ultra-high voltage GIS conductive support base.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: This is an arc-resistant, high-strength, conductive aluminum-zirconium-scandium rare earth alloy. By mass percentage, the composition includes Sc 0.12%–0.30%, Zr 0.08%–0.22%, Ce-Er composite rare earth 0.03%–0.09%, and Ti-B grain refiner 0.01%–0.025%. Impurities are controlled to be Fe≤0.015%, Si≤0.012%, Cu≤0.008%, with the balance being 99.99 wt.% high-purity aluminum. Preferably, by mass percentage, the preferred proportions of each core alloying element are 0.18% to 0.24% Sc, 0.13% to 0.17% Zr, and 0.06% to 0.075% Ce-Er composite rare earth.

[0008] The mass ratio of Ce to Er is 3:1; the mass ratio of Zr to Sc, K1, is controlled between 0.6 and 0.8; after melting, casting, forging, and graded aging heat treatment, L12-type core-shell structure Al3(Sc,Zr,Ce,Er) nano-precipitates are generated in situ inside the alloy matrix. The precipitates are uniformly dispersed and the average particle size is strictly controlled between 5nm and 10nm; the core is Al3Sc and the outer layer is coated with a composite atomic layer of Zr, Ce, and Er. It has excellent high-temperature thermodynamic stability and can simultaneously achieve the triple effects of fine grain strengthening, precipitation strengthening, and arc thermal barrier.

[0009] The alloy's microstructure, electrical conductivity, mechanical strength, and arc erosion resistance are synergistically controlled through three types of quantitative mathematical models: a strength-conductivity synergistic balance model, an arc ablation rate prediction model, and a grain growth limiting factor model. These three coupled mathematical models respectively control conductivity-strength matching, arc ablation loss, and solidification grain size. The synergistic effect of these three models achieves precise and controllable material properties.

[0010] Preferably, the calculation formula corresponding to the intensity-conductivity synergistic balance model is: In the formula, The measured conductivity of the alloy; The conductivity is based on 99.99% high-purity aluminum. For Sc, Zr, and rare earth solid solution atoms, the electron scattering coefficients are given. The conductivity compensation coefficient for the L12 nanoparticle precipitate; The volume fraction of the L12-Al3(Sc,Zr,Ce,Er) core-shell precipitates; The formula represents the total solid solution mass fraction of Sc, Zr, Ce, and Er that has not been desoluble in the aluminum matrix. It is used to quantitatively predict the matching relationship between the alloy's electrical conductivity and the content of precipitated phases and solid solution solutes, so as to achieve simultaneous control of high strength and high conductivity.

[0011] Solid solutions can distort the crystal lattice and reduce conductivity, but during aging, the solute desolvents to form dispersed nano-precipitates, reducing the content of solid solution atoms in the matrix and reducing electron scattering. At the same time, the precipitates provide a strengthening effect. The alloy addition amount and heat treatment regime can be designed in reverse using the formula to simultaneously achieve high tensile strength and high conductivity, breaking the traditional bias of the mutual exclusion between "strength and conductivity" in alloys.

[0012] Preferably, the calculation formula corresponding to the arc ablation rate prediction model is: In the formula, The linear ablation rate of the alloy under UHV GIS short-circuit arc conditions; The reference arc erosion rate for pure aluminum; The arc thermal barrier suppression coefficient of Ce-Er composite rare earth doped nano-precipitates; The volume fraction of the L12-Al3(Sc,Zr,Ce,Er) core-shell precipitates; The average particle size of the nano-precipitated phase; The formula is a natural exponential function; it is used to reverse-engineer the addition of rare earth elements and Sc / Zr in the alloy, controlling the arc ablation rate at an extremely low level. Under the instantaneous high temperature of the arc, the rare earth-containing core-shell precipitates rapidly form a dense, high-temperature resistant composite oxide film, preventing the aluminum matrix from melting and vaporizing. This formula can reverse-engineer the volume fraction and particle size of the precipitates based on the rated short-circuit current index of GIS, accurately controlling the arc ablation loss, and meeting the arc resistance requirements without increasing the component wall thickness.

[0013] The preferred calculation formula for the grain growth limiting factor model is as follows: In the formula, The slope of the liquidus line in aluminum-based alloys; The total mass fraction of the four solute elements Sc, Zr, Ce, and Er added to the melt; is the average distribution coefficient of Sc, Zr, Ce, Er solutes at the aluminum liquid-solid interface; The total grain growth limiting factor of multi-element rare earth aluminum-zirconium-scandium alloy; growth limiting factor The larger the dendrite size, the stronger the nucleation driving force during solidification, and dendrite growth is significantly suppressed. When the temperature is ≥280, the grain size of the casting is ≤25. It completely eliminates micro-shrinkage and porosity defects, solving the problems of internal defects, current-carrying heating, and creep deformation in cast aluminum components from the source.

[0014] A precision casting and forging method for preparing ultra-high voltage GIS conductive support bases based on arc-resistant, high-strength, conductive aluminum-zirconium-scandium rare earth alloys includes the following steps: S1. High-purity aluminum smelting and alloying control: 99.99wt.% high-purity aluminum ingots are heated to 740-760℃ and completely melted. Al-Sc, Al-Zr, Al-Ce, Al-Er master alloys and Al-Ti-B grain refiner are added in sequence and held at that temperature for 20-30 minutes. Online sampling and testing of the total solute content in the melt were conducted. The amount of alloy added was adjusted by the grain growth limitation factor calculation formula to ensure that Q ≥ 280℃・wt.%; Rotary argon gas blowing was used for degassing for 20 minutes, and ceramic foam filters were used to remove inclusions in the melt. S2, Low-pressure semi-solid metal type filling: The purified melt is cooled to a semi-solid temperature range of 690-710℃ and introduced into a special metal mold for GIS conductive support base. The low-pressure filling pressure is 0.035-0.05MPa, the filling rate is 0.7-0.9kg / s, and the pressure is held for 35-45s after filling to obtain a near-net-shape casting billet with a single-sided forging allowance of 0.8-1.2mm. S3, In-situ closed semi-solid forging densification: When the solid fraction of the billet is 75% to 82% and not fully solidified, closed-die forging is carried out in the same set of molds. The forging pressure is 80 to 110 MPa and the pressure is held for 10 to 15 seconds. Coarse dendrites are broken by plastic extrusion, and the internal porosity and shrinkage of the billet are eliminated. S4. Graded temperature-controlled aging heat treatment: The forged blank is first solution-treated at 530–540℃ for 3–4 hours, then rapidly cooled to room temperature by water quenching. A two-stage aging treatment is then performed: a low-temperature pre-aging temperature of 155–165℃ for 3.5–4.5 hours, followed by a high-temperature final aging temperature of 280–295℃ for 5.5–6.5 hours. After aging, the volume fraction of precipitated phases is measured. The conductivity and mechanical properties of the alloy are verified by the strength-conductivity synergistic balance formula. If the properties do not meet the standards, the aging and heat preservation time is finely adjusted. S5. Precision machining and conductive protection treatment: After aging, the forged and cast integrated blank is precision machined by five-axis CNC milling, and the dimensional accuracy is controlled to IT6 level; the conductive contact surface of the support seat is polished to a roughness Ra≤0.8μm, and finally a nano-alumina insulating and wear-resistant coating is sprayed to obtain the finished UHV GIS conductive support seat.

[0015] Preferably, in step S3, the preferred pressure for in-situ closed forging is 90-100 MPa, and the forging holding time is 10-12 s.

[0016] Preferably, in step S4, the preferred two-stage aging process is: pre-aging at 160℃ for 4 hours and final aging at 290℃ for 6 hours.

[0017] Compared with existing technologies, the beneficial effects of this invention are as follows: This invention adopts a scandium-zirconium-cerium-erbium composite rare earth synergistic microalloying system, and is equipped with three sets of exclusive quantitative control models, which effectively overcomes the inherent industry problem of mutual restriction between the strength and conductivity of aluminum alloys. The core-shell nano-precipitates generated inside can simultaneously achieve the dual effects of strengthening the matrix and reducing electron scattering. Relying on the arc erosion prediction model to directionally control the rare earth ratio, a stable high-temperature resistant protective layer can be generated on the surface of the component under arc thermal shock, which significantly weakens arc ablation damage and meets the equipment insulation protection requirements without increasing the cross-sectional size of the component. With the help of the grain quantitative control model and the semi-solid in-situ forging process, internal defects such as porosity and coarse grains are suppressed from the solidification source, and local overheating and creep deformation problems are not easy to occur during long-term current-carrying operation.

[0018] This invention's integrated casting and forging process combines multiple traditional discrete processing steps, simplifies the production chain, reduces residual stress caused by multiple processes, and achieves standardized and precise control throughout the process using a quantitative model. This breaks away from the traditional production mode that relies on manual experience for debugging, significantly improving product consistency and yield. By strictly controlling harmful impurities to avoid the formation of brittle phases, the contact resistance of conductive contact surfaces remains stable over a long period, and temperature rise control is excellent. The entire set of materials and forming processes can be adapted to the large-scale mass production of various UHV GIS conductive support components, and has the comprehensive advantages of controllable production costs, small performance fluctuations, and high equipment reliability. Attached Figure Description

[0019] Figure 1 A schematic diagram of the process for precision casting and forging of high-strength, arc-resistant, conductive aluminum-zirconium-scandium rare earth alloy and its UHV GIS conductive support base. Detailed Implementation

[0020] To provide a further understanding of the purpose, structure, features, and functions of the present invention, detailed descriptions are provided below with reference to specific embodiments.

[0021] Please refer to the reference. Figure 1 This invention provides a method for precision casting and forging of an arc-resistant, high-strength, conductive aluminum-zirconium-scandium rare earth alloy and its ultra-high voltage GIS conductive support base.

[0022] Basic parameter prerequisites: Raw material standard: 99.99 wt.% high-purity aluminum, with maximum impurities of Fe≤0.015%, Si≤0.012%, and Cu≤0.008%; Elemental ratio rules: Ce:Er=3:1, Zr / Sc mass ratio K1=0.6~0.8 Three model constants: Strength-conductivity model: (IACS) = 62.8% (high-purity aluminum reference conductivity). =125, =38 Arc ablation model: =18.2μm / min (pure aluminum arc ablation rate). =420 Grain confinement factor model: =72℃ / wt.% =0.085, the required value is... ≥280 ℃・wt.% Forming equipment: semi-solid low-pressure metal mold, in-situ closed-die forging press, five-axis CNC milling machine, double-stage aging heat treatment. Example 1: Preferred alloy, standard GIS 1100kV conductive support.

[0023] I. Alloy Composition Formula (mass percentage): Sc: 0.21%, Zr: 0.15%, Ce-Er composite rare earth: 0.068%, Ti-B refining agent: 0.018% Impurities: Fe=0.011%, Si=0.009%, Cu=0.006%, balance high-purity aluminum. 1. Proportion verification: K1 = Zr / Sc = 0.15 / 0.21 ≈ 0.714, falling within the range of 0.6 to 0.8; The total Ce-Er ratio is 0.068%, with Ce accounting for 0.051% and Er accounting for 0.017%. The Ce:Er ratio is 3:1, which meets the requirements. The total addition of the four solutes, C0, is calculated as follows: C0 = 0.21 + 0.15 + 0.068 = 0.428 wt.%. 2. Grain growth limiting factor calculate ; satisfy ≥280 index, solidified grain size ≤25μm.

[0024] Complete precision casting and forging process: S1. High-purity aluminum smelting and alloying control: Feeding: 100kg of 99.99% high-purity aluminum ingots are fed into the resistance melting furnace and heated to 750℃ until completely melted; The intermediate alloy was added sequentially: Al-2Sc, Al-10Zr, Al-20Ce, Al-20Er, and Al-5Ti-B, and held at that temperature for 25 minutes. Melt sampling and spectral analysis showed that C0 was 0.428%. =331 meets the standard, no additional alloy is needed; Rotary argon gas was used for degassing for 20 minutes, and ceramic foam board was used to filter out slag inclusions. The total impurities in the melt were 0.032% ≤ 0.04%.

[0025] S2, Low-pressure semi-solid metal type filling: The melt is cooled to the semi-solid range of 700℃ and introduced into a special metal mold for GIS support base; the filling pressure is 0.04MPa, the filling rate is 0.8kg / s, and the pressure is held for 40s after filling is completed; a near-net-shape billet is obtained, with a 1.0mm allowance for single-sided forging, and the solid content of the billet is 78%.

[0026] S3, In-situ closed semi-solid forging densification: The billet is forged in a closed mold with 78% solids content before demolding; the forging pressure is 95MPa (preferred range 90~100MPa), and the pressure is held for 11s; the dendrites are crushed by extrusion, internal shrinkage and porosity are eliminated, and the porosity is reduced to below 0.15%.

[0027] S4. Graded temperature-controlled aging heat treatment: S4.1 Solution treatment: Hold at 535℃ for 3.5 hours, then remove from the furnace and water-cool to room temperature; S4.2 Two-stage aging (optimal process): 160℃ pre-aging for 4 hours → 290℃ final aging for 6 hours; S4.3 Performance Verification (Strength-Conductivity Co-balance Model): Post-aging testing: solid solution solute =0.062 wt.%, Volume fraction of precipitated phase =0.038;

[0028] It has an electrical conductivity of 56.34% IACS and a tensile strength of 412MPa, and there is no problem of mutual repulsion in strength conductivity.

[0029] S4.4 Arc Ablation Rate Verification: The average particle size of the precipitated phase is 7 nm. Substituting this into the arc ablation prediction model:

[0030] The ablation rate is extremely low, and no thickening of components is required under short-circuit arc.

[0031] S5. Precision machining and conductive protection: Five-axis CNC milling and finishing, with overall dimensional accuracy of IT6 level; The conductive contact surface is mirror polished with a roughness Ra=0.6μm≤0.8μm; Electrostatic spraying of a nano-alumina wear-resistant and insulating coating, followed by curing, yields an 1100kV GIS conductive support base.

[0032] Example 2: Low-ratio alloy, 720kV small and medium-sized GIS support base.

[0033] I. Alloy Composition Formula (by weight) Sc: 0.13%, Zr: 0.085%, Ce-Er composite rare earth: 0.035%, Ti-B refining agent: 0.012% Impurities: Fe=0.013%, Si=0.010%, Cu=0.007%, balance high-purity aluminum. 1. Proportion verification K1 = 0.085 / 0.13 ≈ 0.654, in the range of 0.6 to 0.8; Ce = 0.02625%, Er = 0.00875%, ratio 3:1; Total Solute Addition =0.13 + 0.085 + 0.035 = 0.25 wt.% Value verification: ; If the requirement is not met, add Al-Sc master alloy to increase Sc to 0.175% and recalculate: =0.175 + 0.085 + 0.035 = 0.295 wt.% ; Still insufficient and not up to standard, add Ce-Er rare earth to bring the total to 0.052%, and recalculate: =0.175 + 0.085 + 0.052 = 0.312 wt.% ; If the result is still insufficient, add a small amount of Zr to bring the total to 0.10%, and recalculate. =0.175 + 0.10 + 0.052 = 0.327 wt.% ; Still insufficient, Sc is increased to 0.19%, and the calculation is repeated: =0.19 + 0.10 + 0.052 = 0.342 wt.% ; Finally, a small amount of Ti-B was added to further refine the process. Eventual stability =286, which meets the requirement of ≥280.

[0034] Sc-Zr-Ce-Er System Foundation Less than 280 → Utilizing Ti element for ultra-high single element Gain characteristics → Micro-addition of Ti-B, dissolved Ti as the fifth solute linearly boosts the overall gain. → Total The value increased to 286, meeting the threshold; simultaneously, TiB2 solid particles provided a large number of heterogeneous nuclei, which, along with high... It synergistically achieves an ultrafine, defect-free as-cast microstructure, with extremely low Ti addition, without sacrificing the core properties of conductivity and arc resistance.

[0035] II. Fine-tuning of casting and forging processes to adapt to smaller product specifications: S1. Melting: Melt at 740℃, hold for 20 minutes, and degas with argon for 20 minutes; S2, Semi-solid filling: 690℃, filling pressure 0.035MPa, filling rate 0.7kg / s, holding pressure 35s, single-sided margin 0.8mm; S3, In-situ forging: Pressure 80MPa, holding pressure for 10s; S4. Heat treatment: Solution treatment at 530℃ for 3 hours; pre-aging at 155℃ for 3.5 hours; final aging at 280℃ for 5.5 hours. Timeliness testing =0.075wt.% =0.029, =9nm; Electrical conductivity: =62.8-125×0.075+38×0.029=54.04% IACS Arc erosion rate:

[0036] S5, Finishing: IT6 precision, contact surface Ra=0.7 Nano-alumina coating for protection.

[0037] The present invention has been described in the above-described embodiments; however, these embodiments are merely examples for implementing the present invention. It must be noted that the disclosed embodiments do not limit the scope of the present invention. Conversely, any modifications and refinements made without departing from the spirit and scope of the present invention are within the scope of patent protection of the present invention.

Claims

1. An arc-resistant, high-strength, conductive aluminum-zirconium-scandium rare-earth alloy, characterized in that: By mass percentage, the components include Sc 0.12%–0.30%, Zr 0.08%–0.22%, Ce-Er composite rare earth 0.03%–0.09%, and Ti-B grain refiner 0.01%–0.025%; Impurities are controlled to be Fe≤0.015%, Si≤0.012%, Cu≤0.008%, with the balance being high-purity aluminum with a purity of 99.99 wt.%; the mass ratio of Ce to Er is 3:1; the mass ratio K1 of Zr to Sc is controlled between 0.6 and 0.8; L12-type core-shell structure Al3(Sc,Zr,Ce,Er) nano-precipitates are generated in situ inside the alloy matrix, with a particle size range of 5 nm to 10 nm; the microstructure, electrical conductivity, mechanical strength, and arc corrosion resistance of the alloy are synergistically regulated by three types of quantitative mathematical models, including a strength-conductivity synergistic balance model, an arc ablation rate prediction model, and a grain growth limiting factor model.

2. The arc-resistant, high-strength, conductive aluminum-zirconium-scandium rare earth alloy as described in claim 1, characterized in that: The preferred proportions of each core alloying element by mass percentage are Sc 0.18%–0.24%, Zr 0.13%–0.17%, and Ce-Er composite rare earth 0.06%–0.075%.

3. The arc-resistant, high-strength, conductive aluminum-zirconium-scandium rare earth alloy as described in claim 1, characterized in that: The calculation formula corresponding to the strength-conductivity synergistic balance model is: In the formula, The measured conductivity of the alloy; The conductivity is based on 99.99% high-purity aluminum. For Sc, Zr, and rare earth solid solution atoms, the electron scattering coefficients are given. The conductivity compensation coefficient for the L12 nanoparticle precipitate; The volume fraction of the L12-Al3(Sc,Zr,Ce,Er) core-shell precipitates; The formula represents the total solid solution mass fraction of Sc, Zr, Ce, and Er that has not been desoluble in the aluminum matrix. It is used to quantitatively predict the matching relationship between the alloy's electrical conductivity and the content of precipitated phases and solid solution solutes, so as to achieve simultaneous control of high strength and high conductivity.

4. The arc-resistant, high-strength, conductive aluminum-zirconium-scandium rare earth alloy as described in claim 1, characterized in that: The calculation formula corresponding to the arc ablation rate prediction model is: In the formula, The linear ablation rate of the alloy under UHV GIS short-circuit arc conditions; The reference arc erosion rate for pure aluminum; The arc thermal barrier suppression coefficient of Ce-Er composite rare earth doped nano-precipitates; The volume fraction of the L12-Al3(Sc,Zr,Ce,Er) core-shell precipitates; The average particle size of the nano-precipitated phase; It is a natural exponential function; the formula is used to reverse-engineer the rare earth and Sc / Zr addition amounts in alloys to control the arc ablation rate at an extremely low level.

5. The arc-resistant, high-strength, conductive aluminum-zirconium-scandium rare earth alloy as described in claim 1, characterized in that: The calculation formula corresponding to the grain growth limiting factor model is: In the formula, The slope of the liquidus line in aluminum-based alloys; The total mass fraction of the four solute elements Sc, Zr, Ce, and Er added to the melt; is the average distribution coefficient of Sc, Zr, Ce, Er solutes at the aluminum liquid-solid interface; is the total grain growth limiting factor of multi-element rare earth aluminum-zirconium-scandium alloy.

6. A precision casting and forging method for preparing ultra-high voltage GIS conductive support bases based on the arc-resistant, high-strength, conductive aluminum-zirconium-scandium rare earth alloy according to any one of claims 1 to 5, characterized in that: It includes the following steps: S1. High-purity aluminum smelting and alloying control: 99.99wt.% high-purity aluminum ingots are heated to 740-760℃ and completely melted. Al-Sc, Al-Zr, Al-Ce, Al-Er master alloys and Al-Ti-B grain refiner are added in sequence and held at that temperature for 20-30 minutes. Online sampling and detection of the total solute content of Sc, Zr, Ce, and Er in the melt, and substituting these into the grain growth restriction factor formula for calculation. The value was adjusted by finely controlling the amount of intermediate alloy added to ensure Q ≥ 280℃・wt.%; rotary argon gas blowing was used for degassing for 20 minutes, and ceramic foam filters were used to remove oxide inclusions from the melt, controlling the total impurity content of the melt to ≤ 0.04%; S2, Low-pressure semi-solid metal type filling: The purified melt is cooled to a semi-solid temperature range of 690-710℃ and introduced into a special metal mold for GIS conductive support base. The low-pressure filling pressure is 0.035-0.05MPa, the filling rate is 0.7-0.9kg / s, and the pressure is held for 35-45s after filling to obtain a near-net-shape billet with a single-sided forging allowance of 0.8-1.2mm. S3, In-situ closed semi-solid forging densification: When the solid fraction of the billet is 75% to 82% and not fully solidified, closed-die forging is carried out in the same set of molds. The forging pressure is 80 to 110 MPa and the pressure is held for 10 to 15 seconds. Coarse dendrites are broken by plastic extrusion, and the internal porosity and shrinkage of the billet are eliminated. S4. Graded temperature-controlled aging heat treatment: The forged blank is first solution-treated at 530–540℃ for 3–4 hours, then rapidly cooled to room temperature by water quenching. A two-stage aging treatment is then performed: a low-temperature pre-aging temperature of 155–165℃ for 3.5–4.5 hours, followed by a high-temperature final aging temperature of 280–295℃ for 5.5–6.5 hours. After aging, the volume fraction of precipitated phases is measured. The conductivity and mechanical properties of the alloy are verified by the strength-conductivity synergistic balance formula. If the standard is not met, the aging and heat preservation time is finely adjusted. S5. Precision machining and conductive protection treatment: After aging, the forged and cast integrated blank is precision machined by five-axis CNC milling, and the dimensional accuracy is controlled to IT6 level; the conductive contact surface of the support seat is polished to a roughness Ra≤0.8μm, and finally a nano-alumina insulating and wear-resistant coating is sprayed to obtain the finished UHV GIS conductive support seat.

7. The method for precision casting and forging of the UHV GIS conductive support base as described in claim 6, characterized in that: In step S3, the preferred pressure for in-situ closed forging is 90-100 MPa, and the forging holding time is 10-12 s.

8. The method for precision casting and forging of the UHV GIS conductive support base as described in claim 6, characterized in that: In step S4, the preferred two-stage aging process is as follows: pre-aging at 160℃ for 4 hours and final aging at 290℃ for 6 hours.